Essential Oil Composition of Root of Ferula assa-foetida from Two Iranian Localities (Gonabad and Tabas) - HADAVAND MIRZAEI, Hossein; Hasanloo, Tahereh (Asian Journal of Chemistry, 2010)
Hydrodistilled oils of Ferula assa-foetida root were collected from two Iranian ecotypes (Gonabad and Tabas) and analyzed by GC and GC/MS system. The results of essential oils analysis showed the presence of 32 compounds. A total of 26 compounds constituting of 98.5 % oil were characterized in Gonabad sample and 26 compounds constituting of 93.3 % oil identified in Tabas sample. According to present results, both samples showed similar chemical compositions, the dominant components in both samples were E-1-propenyl sec-butyl disulfide (30.7 and 18.8 % in Gonabad and Tabas samples, respectively), Z-1-propenyl secbutyl disulfide (12.4 and 9.2 % in Gonabad and Tabas samples, respectively), eudesmol (10-epi-γ) (12.7 and 18.7 % in Gonabad and Tabas samples, respectively), methyl 1-(methylthio) propyl disulfide (10.9 and 4.3 %), eudesmol (7-epi-α) (4.8 and 8.2 % in Gonabad and Tabas samples, respectively) and agarospirol (2.8 and 5.1 % in Gonabad and Tabas samples, respectively).